2017
DOI: 10.3389/fmicb.2017.00829
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene-expression Analysis of the Response of Salmonella Enteritidis to Egg White Exposure Reveals Multiple Egg White-imposed Stress Responses

Abstract: Chicken egg white protects the embryo from bacterial invaders by presenting an assortment of antagonistic activities that combine together to both kill and inhibit growth. The key features of the egg white anti-bacterial system are iron restriction, high pH, antibacterial peptides and proteins, and viscosity. Salmonella enterica serovar Enteritidis is the major pathogen responsible for egg-borne infection in humans, which is partly explained by its exceptional capacity for survival under the harsh conditions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 170 publications
14
35
2
Order By: Relevance
“…However, revelation of this resistance mechanism requires further determination of the yoaE function, which is as yet still unclear. CpxR/A is a critical TCS contributing to the survival of S. Enteritidis in egg white and functions by extensively regulating genes that help bacteria resist envelope stress and alkaline pH (16,17). In the present study, we proved that yoaE gene is a CpxR/A regulon and that this regulatory relationship should be conserved in neighboring species, indicating that yoaE should be envelope stress-related gene, which provides clues to the yoaE gene function.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, revelation of this resistance mechanism requires further determination of the yoaE function, which is as yet still unclear. CpxR/A is a critical TCS contributing to the survival of S. Enteritidis in egg white and functions by extensively regulating genes that help bacteria resist envelope stress and alkaline pH (16,17). In the present study, we proved that yoaE gene is a CpxR/A regulon and that this regulatory relationship should be conserved in neighboring species, indicating that yoaE should be envelope stress-related gene, which provides clues to the yoaE gene function.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that S. Enteritidis mobilizes utilizes multiple mechanisms to counteract antibacterial factors in egg white. Genes or pathways involved in iron absorption (15)(16)(17), biotin synthesis (16)(17)(18), DNA replication and repair (4,17,19), alkaline pH adaptation (17), osmotic stress adaptation (17), envelope damage repair (including peptidoglycan biosynthesis and remodeling) (4,17), amino acid transport and metabolism (4), lipopolysaccharide metabolism (4,18,20,21), and cell motility (22) were found to be important for S. Enteritidis survival in egg white.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is increasing evidence implicating the role of enterobactin in bacterial stress responses. For example, enterobactin biosynthesis and uptake were induced following exposure of S. Enteritidis to egg white to facilitate iron acquisition, thus providing a survival advantage to this bacterium (16,49). Peralta et al found that enterobactin protected E. coli against oxidative stress and that this effect was independent of its capacity to scavenge iron (50).…”
Section: Resultsmentioning
confidence: 99%
“…The biotin synthase gene bioB is required for the survival of Salmonella Enteritidis in egg whites ( Raspoet et al, 2014 ). Moreover, bioA, B, C, D , and F are transcriptionally upregulated in Salmonella Enteritidis during growth in whole egg or egg white model medium ( Jakociune et al, 2016 ; Baron et al, 2017 ). In our study, the single nucleotide variation (T433G, S145A) in the bioC gene was predicted to be deleterious in silico and suggested that this nsSNP had drastic functional consequences ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%